2020
DOI: 10.21101/cejph.a5942
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with standard precautions in inpatient healthcare settings in the Czech Republic: a cross-sectional survey

Abstract: Objective: The study evaluates compliance with declared hygienic standards carried out by healthcare professionals in clinical practice within their scope of direct patient care and the maintenance of medical tools and devices in healthcare facilities in the Czech Republic.Methods: Cross-sectional questionnaire study focused on the standards of safe health care. All 80 addressed healthcare providers were also involved in the 2018 Adverse Event Reporting System (AERS) pilot project. Responses were scored on a 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…Regarding awareness and compliance, safe injection practice showed high scores, which supports the results of previous studies (Pokorná et al, 2020). Further, knowledge was found to be higher in those who had experienced a needle-prick injury.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regarding awareness and compliance, safe injection practice showed high scores, which supports the results of previous studies (Pokorná et al, 2020). Further, knowledge was found to be higher in those who had experienced a needle-prick injury.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, this study found that workers in long-term stay institutions in closed wards had less knowledge on standard precautions. In a study targeting physicians, psychiatry had the lowest knowledge on infection compared to other fields, and it was expressed as a negative phenomenon (Pokorná et al, 2020). These studies and our study may highlight the reality of the knowledge of infection among psychiatric health care professionals.…”
Section: Discussionsupporting
confidence: 48%
“…In our followed sample, we observed that general nurses disinfect their hands before using PPE 1.25 times more (53.3%) than physicians (42.4%) and 2.6 times more often than other health care workers (20.2%). Pokorná et al14 published similar results in her questionnaire in 2018.…”
Section: Discussionmentioning
confidence: 54%
“…A cross-sectional survey on compliance with hand hygiene was conducted via online questionnaire in health care facilities in the Czech Republic (Pokorná et al, 2020). The standardized questionnaire "Standard precautions" (hereinafter referred to as SP) was used for data collection (Efstathiou et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The records without any response were excluded from the evaluation using the Kruskal-Wallis test. The differences in responses between the compared groups were considered significant if pK and pI were < 0.05 (Pokorná et al, 2020).…”
Section: Methodsmentioning
confidence: 99%